Wpływ kompetencji strategicznych kadry menedżerskiej na konkurencyjność i rozwój agrobiznesu - Firlej, Krzysztof (Influence of Strategic Competence of the Managerial Staff on Competitiveness and Development of Agribusiness, 2005)
The management strategy is nowadays a decisive factor in an enterprise's market value. The value of human assets in an enterprise determines its position on the market and directs its development. The strategic congruence of intellectual capital plays a vital role as the foundations of the strategic competence of the managerial staff. The economic units that function in all areas of Polish agribusiness need to be prepared to face competition on the European market through acquiring and employing valuable human capital. The article suggests that the issue in question needs to be given the highest priority as it is one of the most important in agribusiness enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 210-218